2019
DOI: 10.1021/acs.jpcc.8b12269
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Geometry-Controlled Mechanical Properties of Spiral Carbon-Based Nanostructures

Abstract: The spiral structures of carbon-based materials such as coiled carbon nanotube (CCNT) and graphene helicoid have attracted great attention for use in electrical and mechanical nanodevices. There are a couple of main reasons for this attitude such as striking properties and behavioral diversity with regard to the ever-increasing need for miniaturization of devices. In this research, using atomistic simulations, the effects of geometric parameters (e.g., cross-sectional shape, pitch angle, inner diameter, and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…All the atomic structures of coiled CNTs with various parameters via PFC modeling can be found at https://github.com/YanChen32/Coiled‐carbon‐nanotubes.git. Compared with previous works, [ 32,46 ] the atomic structures of coiled CNTs obtained by PFC modeling possess more perfect and smooth helical configurations, covering an arbitrary combination of geometrical parameters, i.e., CNT radius r , coil pitch l , and coil radius R , as shown in Figure 1c.…”
Section: Models and Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…All the atomic structures of coiled CNTs with various parameters via PFC modeling can be found at https://github.com/YanChen32/Coiled‐carbon‐nanotubes.git. Compared with previous works, [ 32,46 ] the atomic structures of coiled CNTs obtained by PFC modeling possess more perfect and smooth helical configurations, covering an arbitrary combination of geometrical parameters, i.e., CNT radius r , coil pitch l , and coil radius R , as shown in Figure 1c.…”
Section: Models and Methodsmentioning
confidence: 87%
“…The vdW‐induced nonuniform deformation and phase transformations are widely investigated for coiled CNTs. [ 18,32,51 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not surprising that this should also be a common motif observed in carbon nanostructures . Because of their unique 3D helical morphology, relatively high electrical conductivity, , large surface area, high-performance electromagnetic wave absorption, , and superelasticity, coiled carbon nanotubes (CCNTs) are applicable in a variety of fields such as electrocatalysts for fuel cells, supercapacitor electrodes, , reinforcement, , biological sensors, hydrogen storage materials, , and chiral catalysts . In mechanics, the ability of CCNTs to elastically sustain loads at large deflections allows them to store or absorb significant amounts of strain energy.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it can be concluded that the tensile properties of CCNTs are strongly dependent on the geometry and the chirality of CNTs. It should, however, be noted that many questions have remained without any answer regarding the mechanical properties of CCNTs. Due to the complex stress distribution in the tensile test of CCNTs and the infinite number of possible structures, the accurate mathematical expression of mechanical properties as a function of geometrical parameters is not well identified and formulated as yet.…”
Section: Introductionmentioning
confidence: 99%